Epistemic Sovereignty and Dual Hegemony in Salaf Pesantren Resistance to Educational Modernity in Jember - Ach Barocky Zaimina; Aminullah; Mohammad Mu'tashim Billah (Nadwa: Jurnal Pendidikan Islam, 2026)
The encounter between Salaf Pesantren and educational modernity represents a critical issue in contemporary Islamic education because it shapes traditional epistemology, institutional autonomy, and pesantren identity. Previous scholarship has extensively examined pesantren modernization, curriculum reform, and institutional adaptation; however, limited attention has been paid to how resistance functions as a strategy for preserving epistemic sovereignty. This study explores how Salaf pesantren in Jember Regency construct resistance to educational modernity. Employing a comparative qualitative case study design, the research was conducted at three Salaf pesantren: Al-Wafa Temporan, Salafiyah Curah Kates Ajung, and Raudlatul Ulum Sumber Wringin. Data were collected through staged interviews, field observations, and document analysis and analyzed using data reduction, thematic coding, and cross-case comparison. The findings identify three models of resistance: absolutist resistance, reforming resistance, and accommodative-reforming resistance. These models are sustained through the preservation of kitab kuning, the authority of the kyai, moral discipline, spatial regulation, technological restrictions, and economic self-reliance. The study argues that resistance is not merely opposition to modernity but a strategy for maintaining epistemic sovereignty through a dual hegemonic structure interpreted within a Foucauldian framework. It further proposes a policy framework based on partnership without intervention that respects pesantren autonomy while supporting context-sensitive modernization.